2008
DOI: 10.1002/asi.20994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on methods of detecting research fronts using different types of citation

Abstract: In this article, we performed a comparative study to investigate the performance of methods for detecting emerging research fronts. Three types of citation network, co-citation, bibliographic coupling, and direct citation, were tested in three research domains, gallium nitride (GaN), complex network (CNW), and carbon nanotube (CNT). Three types of citation network were constructed for each research domain, and the papers in those domains were divided into clusters to detect the research front. We evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(82 citation statements)
references
References 25 publications
0
80
0
2
Order By: Relevance
“…In Fig. 2, there is bibliographic coupling between F and G, as they both cite D. Recent studies have validated the performance of these methods to detect emerging research front [66,12] and investigated citation networks with combinational types of citations, such as including direct citations and co-citations to exploit new possibilities of detecting research fronts [32]. The concept of indirect citations proposed in this paper differs from these studies, as described in our example referring to Fig.…”
Section: Citation Networkmentioning
confidence: 97%
“…In Fig. 2, there is bibliographic coupling between F and G, as they both cite D. Recent studies have validated the performance of these methods to detect emerging research front [66,12] and investigated citation networks with combinational types of citations, such as including direct citations and co-citations to exploit new possibilities of detecting research fronts [32]. The concept of indirect citations proposed in this paper differs from these studies, as described in our example referring to Fig.…”
Section: Citation Networkmentioning
confidence: 97%
“…Her iki veri tabanı da genel amaçlı bilimsel yayınların atıf istatistikleri ve yayınların bibliyografik verilerine erişim imkanı sağlamaktadır (Meho ve Yang, 2007). Atıf analizi yöntemi gereği veri seti içindeki atıf bilgilerinin bilimsel anlamda tutarlı ve geçerli olması analizin ön şartını oluşturmaktadır (Shibata, Kajikawa, Takeda ve Matsushima, 2009). Bu özellikler dikkate alındığında Google Akademik veri tabanı daha fazla yayına erişim imkanı sağlamasına rağmen tutarlılık ve güvenirlik kriterleri nedeniyle kapsam dışı bırakılmıştır (Mikki, 2009).…”
Section: Veri Derleme Stratejisiunclassified
“…The clustering of citation networks to study research specialties has been pioneered by Small (1973) based on a subset of highly cited documents and using co-citation instead of direct citations. Recently, Shibata et al (2009) conducted a comparison of direct citation, co-citation, and bibliographic coupling to detect research fronts, and concluded that direct citation outperformed the other two approaches in detecting research fronts as it identified large and emerging clusters earlier. In addition, they observed that direct citation networks had the largest clustering coefficients, an indication of higher content similarity.…”
Section: Appendix: Explanation Of Terms Usedmentioning
confidence: 99%